Self- Control dan Internet addiction pada Mahasiswa: Pendekatan Structural Equation Modeling: Self-control and Internet addiction in College Students: A Structural Equation Modeling Approach - Mutiah, Diana; Bintang, Rahmat S.; Putri, Vika Adelia; Zainuddin, Nurul Inayah (Persona:Jurnal Psikologi Indonesia, 2024)
The overuse of the internet is known as internet addiction. People who are addicted to the internet frequently require assistance in controlling their usage, which causes them to lose track of time and prefer the virtual world to the actual one. The purpose of this study is to look at how self-control affects college students' internet addiction. 352 students, aged between 18 and 24 (M = 20.46, SD = 1.31), living in Jakarta, Bogor, Depok, Tangerang, and Bekasi, made up the sample. There were 69 male students and 283 female students. Purposive sampling, a non-probability technique, was employed. Confirmatory factor analysis (CFA) is used in the construct validity assessment process. The structural equation modeling method is employed to test hypotheses. The results showed that data with an RMSEA value of 0.074 supported the fit model. In addition, there is a significant influence of self-control on internet addiction in students with an opposing direction of influence. The R-square of 40.2% obtains the amount of influence.